Microstructural changes in CoCrFeMnNi under mild tribological load - Dollmann, Antje; Kauffmann, Alexander; Heilmaier, Martin; Haug, Christian; Greiner, Christian (Journal of materials science, 2020)
The lack of a principle element in high-entropy alloys (HEA) leads to unique and unexpected material properties. Tribological loading of metallic materials often results in deformed subsurface layers. As the microstructure feedbacks with friction forces, the microstructural evolution is highly dynamic and complex. The concept of HEAs promises high solid solution strengthening, which might decrease these microstructural changes. Here, we experimentally investigated the deformation behavior of CoCrFeMnNi in a dry, reciprocating tribological contact under a mild normal load. After only a single stroke, a surprisingly thick subsurface deformation layer was observed. This layer is characterized by nanocrystalline grains, twins and bands of localized dislocation motion. Twinning was found to be decisive for the overall thickness of this layer, and twin formation within the stress field of the moving sphere is analyzed. The localization of dislocation activity, caused by planar slip, results in a grain rotation. Fragmentation of twins and dislocation rearrangement lead to a nanocrystalline layer underneath the worn surface. In addition, oxide-rich layers were found after several sliding cycles. These oxides intermix with the nanocrystalline layer due to material transfer to the counter body and re-deposition to the wear track. Having revealed these fundamental mechanisms, the evolution of such deformation layers in CoCrFeMnNi under a tribological load might lead to other HEAs with compositions and properties specifically tailored to tribological applications in the future.